The “Self-Sacrifice” of ImmuneCells in Sepsis - Wen, Xiaoyue; Xie, Bing; Yuan, Shiying; Zhang, Jiancheng (Frontiers in Immunology, 2022)
Sepsis is a life-threatening organ dysfunction caused by the host’s malfunctioning response to infection. Due to its high mortality rate and medical cost, sepsis remains one of the world’s most intractable diseases. In the early stage of sepsis, the over-activated immune system and a cascade of inflammation are usually accompanied by immunosuppression. The core pathogenesis of sepsis is the maladjustment of the host’s innate and adaptive immune response. Many immune cells are involved in this process, including neutrophils, mononuclear/macrophages and lymphocytes. The immune cells recognize pathogens, devour pathogens and release cytokines to recruit or activate other cells in direct or indirect manner. Pyroptosis, immune cell-extracellular traps formation and autophagy are several novel forms of cell death that are different from apoptosis, which play essential roles in the progress of sepsis. Immune cells can initiate “self-sacrifice” through the above three forms of cell death to protect or kill pathogens. However, the exact roles and mechanisms of the self-sacrifice in the immune cells in sepsis are not fully elucidated. This paper mainly analyzes the self-sacrifice of several representative immune cells in the forms of pyroptosis, immune cell-extracellular traps formation and autophagy to reveal the specific roles they play in the occurrence and progression of sepsis, also to provide inspiration and references for further investigation of the roles and mechanisms of self-sacrifice of immune cells in the sepsis in the future, meanwhile, through this work, we hope to bring inspiration to clinical work.